Patrols, records and pictures: Demonstrations of Europe in the midst of migration's crisis. (August 2019) - van Reekum, Rogier
Migration is not readily seen. A vast infrastructure supports its visualization, making migration visible and actionable. Recent scholarship on the visuality of migration has clearly shown how visualizing migration is an integral part of governing it. Concepts and research approaches from Science and Technology Studies (STS) are particularly appropriate when studying these connections between knowing and doing. In this paper, the performativity of visual methods and their data practices are analysed with respect to the monitoring infrastructure of European border management. Three such methods – patrolling, recording and publicizing – are reconstructed through analysis of their histories and their present. Patrolling involves the tactical domination of terrains. Recording involves the production of documentary objectivity. Publicizing involves the pictorial capture of fleeting realities. These methods are irreducibly political. Their political significance is explored through the concept of demonstrative effects that helps to show how methods of visualising migration at once involve specific demonstrations of the European association that is operative in them. These demonstrations make visible what Europe can and cannot do. The so-called 'migration crisis' of Europe turns out to be more than political discourse but entangled with the very methods that render migration apparent and governable.